THE USE OF CHART ON STUDENTS ABILITY TO WRITE EXPLANATION TEXT - Suhartini, Ade; Herawati, Atti; Irdiyansyah, Iyan (Journal of English Teaching and Linguistics Studies (JET Li), 2020)
It is not doubt that writing has important role in real life.  People can communicate, give information, and share their ideas through written way. Writing is classified as difficult skill because there are some components that should be considered, some kinds of text that should be understood, some steps that should be done, etc. Many students face difficulty to write explanation text, especially for generating the ideas. For that reason, chart is chosen as the media. The aim of this research is to find out the use of chart on students ability to write explanation text. It is conducted to the eleventh grade students of SMA Negeri 2 Jonggol. In this research, Pre Experimental method and Pre-test Post-test Group design are used. There are 36 students from class XI MIPA 1 taken as the sample by using random sampling. The data were taken from pre-test and post-test which were analyzed by using t-test formula after having the normal data. Based on the data calculation, the mean of gain is 20.04, and the total of deviation of gain is 9.46. Moreover, t-test value is 9.45. Meanwhile, t-table value is 2.03 at significant level 0.05 with the degree of freedom (df) is 35. In this case, the t-test value is higher than that of the t-table value (9.45 more than 2.03). It means that null hypothesis (Ho) is rejected. Therefore, the use of chart affects students ability to write explanation text.